TEKANAN, SISTEM PENGENDALIAN INTERNAL, BUDAYA ORGANISASI, KOMPETENSI, GAYA KEPEMIMPINAN, PERILAKU TIDAK ETIS TERHADAP POTENSI FRAUD DANA DESA DI KABUPATEN BOYOLALI - Alfian Indra Ningrum; Banu Witono; Zulfikar (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to determine the influence of pressure, internal control systems, organizational culture, competence, leadership style, and unethical behavior on the potential for village fund fraud in Boyolali Regency. Using a quantitative approach, data were collected from a sample of village officials through convenience sampling techniques. The data were analyzed using multiple regression analysis. The results of the study indicate that pressure has a positive influence on the potential for village fund fraud; internal control systems have a significant negative influence on the potential for village fund fraud; organizational culture does not have a significant influence on the potential for village fund fraud; competence has a negative influence on the potential for village fund fraud; leadership style has no influence on the potential for village fund fraud; and unethical behavior has a positive influence on the potential for village fund fraud.